Accommodating to English‐medium instruction in teacher education in Finland. (12th December 2014) - Hahl, Kaisa; Järvinen, Heini‐Marja; Juuti, Kalle
Abstract : This study analyses teacher educators' and student teachers' perceptions of teaching and learning situations in an international English as a lingua franca (ELF) context in an English‐medium instruction (EMI) teacher education programme in Finland. The analysis of semi‐structured interviews revealed that the participants perceived a partial reversal of traditional teacher and student roles; students assisted voluntarily and teaching became reciprocal. Some teachers reflected on having used typical strategies in ELF context, such as code‐switching, to further communication and engage students. However, teachers' lack of fluency was sometimes considered causing frustration among students and affected negatively their feeling of being professional teacher educators. Nevertheless, by increasing more learner‐led activities, ELF can positively affect teacher education pedagogy. Abstract : Artikkelissa tarkastellaan opettajankouluttajien ja opettajaksi opiskelevien käsityksiä opetuksesta ja opiskelusta kansainvälisessä englanninkielisessä opettajankoulutuksessa Suomessa. Opettajien ja opiskelijoiden teemahaastatteluista ilmeni, että perinteisten opettaja‐ ja opiskelijaroolien havaittiin vaihtuneen osittain päinvastaisiksi opetuksessa, jossa kielenä oli lingua franca ‐englanti (ELF); opiskelijat tarjosivat apuaan oma‐aloitteisesti, ja opetuksesta tuli tavanomaista vastavuoroisempaa. Jotkut opettajat kertoivat käyttäneensä tyypillisiä ELF‐kontekstin strategioita, kuten koodinvaihtoa, lisätäkseen kommunikaatiota ja opiskelijoiden osallistumista. Opiskelijat kokivat joskus turhautumista opettajankouluttajan kielellisen sujuvuuden puutteen vuoksi. Opettajankouluttajat puolestaan kokivat kielellisen sujuvuuden puutteen heikentävän ammatillisuuttaan. Opiskelijakeskeisiä työtapoja lisäämällä ELF voi kuitenkin vaikuttaa myönteisesti opettajankoulutukseen.